EPID-36. ANTIDEPRESSANT DRUG USE IN GLIOBLASTOMA PATIENTS: AN EPIDEMIOLOGICAL VIEW. (9th November 2020) - Gramatzki, Dorothee; Rogers, James; Neidert, Marian; Hertler, Caroline; Rhun, Emilie Le; Roth, Patrick; Weller, Michael
Abstract: PURPOSE: Antidepressant drugs have shown anti-tumor activity in preclinical glioblastoma studies. Antidepressant drug use, as well as its association with survival, in glioblastoma patients has not been well characterized on a population level. METHODS: Patient characteristics, including the frequency of antidepressant drug use, were assessed in a glioblastoma cohort diagnosed in a 10-year time-frame between 2005 and 2014 in the Canton of Zurich, Switzerland. Cox proportional hazards regression models were applied for multivariate analysis. Kaplan-Meier survival curves were used to estimate overall survival data and the log-rank test was performed for comparisons. RESULTS: Four hundred four patients with isocitrate dehydrogenase (IDH) wildtype glioblastoma were included in this study. Sixty-five patients (16.1%) took antidepressant drugs at some point during the disease course. Patients were most commonly prescribed selective serotonin reuptake inhibitors at any time (N=46, 70.8%). Nineteen patients (29.2%) were on antidepressant drugs at the time of their tumor diagnosis. No differences were observed in overall survival between those patients who had taken antidepressants at some point in their disease course and those who had not (p=0.356). These data were confirmed in a multivariate analysis including age, Karnofsky performance status, gender, extent of resection, O 6 -methylguanine DNA methyltransferase (MGMT) promoter methylation status, and first-line treatment as cofounders (p=0.315). Also, there was no association of use of drugs modulating voltage-dependent potassium channels (citalopram; escitalopram) with survival (p=0.639). CONCLUSIONS: This signal-seeking study does not support the hypothesis that antidepressants have antitumor efficacy in glioblastoma on a population level.